Plasma Concentrations of Benzylpenicillin and Cloxacillin in Infective Endocarditis—With Special Reference to Delayed Hypersensitivity Reactions - Malin Hägglund; Ulrika Snygg-Martin; Lars Olaison; Michael Stofkoper; Bert Ove Larsson; Magnus Brink (Antibiotics)
Background: Current antibiotic regimens for infective endocarditis (IE) are effective but pose a high risk of delayed hypersensitivity reactions (DHR). Dose adjustments guided by therapeutic drug monitoring (TDM) could mitigate these risks while maintaining treatment efficacy. This study aimed to investigate the plasma concentration of benzylpenicillin and cloxacillin in patients with IE and explore associations between antibiotic concentrations and DHR. Methods: Plasma concentrations of benzylpenicillin and cloxacillin were measured as centre (midpoint concentrations between consecutive doses) and trough values during the first and third weeks of treatment in patients with IE. Patient characteristics and outcomes, including DHR, were documented. Results: A total of 55 patients were included, with 37 patients (67%) receiving benzylpenicillin and 18 (33%) receiving cloxacillin. The 90-day mortality rate was 3%. Both centre and trough concentration exhibited substantial interpatient variation for the two antibiotics, while intra-patient variability between weeks 1 and 3 remained low for most patients. Kidney function could explain, at best, 54% of the variation, and a multiple regression model including kidney function, body mass index, age, and albumin explained up to 68% of the variation for benzylpenicillin. There was no relation between high plasma concentration and the prevalence of DHR; conversely, we observed a tendency of low plasma concentrations in these patients. Conclusions: This study revealed significant interindividual variation in plasma concentrations for both studied penicillins. TDM might be useful in situations where concentrations are hard to predict, such as severe obesity or kidney failure. Additionally, we found no indication that high plasma concentrations are related to the prevalence of DHR.